THE ROLE OF ADVERTISEMENTS IN BUILDING OF PUBLIC RELATIONS IN INDIA - Yogesh M S (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Abstract: Public relations deals with the relationship between the people and the activities of the government. Citizens have many different demands from the government. The government communicates its work and plans to the citizens. There are many ways to communicate the people about the functioning of the government. Advertising is an important tool among them. Public relations are organized according to morality and law. Public relations depend on truth and action and include calm, patience and good humor. If false advertising is given to the people, a criminal case can be registered. The law supports the registration of cases from sections 499 to 522 of the Indian Penal Code of 1860. The government itself understands its objectives and achievements through the media, public opinions, newspapers, telephone, elections, helplines, advertisements and other means. Among these, the largest area of ​​public relations is advertising. Advertising informs the people about the status of education, health, sanitation, environment, irrigation, agriculture, industry, etc. In this context, the research paper is important. In India, there are 462 million social media users, while television viewers are 97 percent. In India, there are 34.90 million email users and 820 million online users.